Insidensi dan Distribusi Penderita Angular Cheilitis pada Bulan Oktober-Desember Tahun 2015 di RSGM Universitas Jember (Incidence and Distribution of Angular Cheilitison October-December 2015 at DentalHospital of Jember University) - Herlin Sriwahyuni; Sri Hernawati; Ayu Mashartini (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Background: The high prevalence, complexity and negative impacts of angular cheilitis are affecting the patient quality of life indicates the importance of the disease caring and treating. Collecting data is required to identifying the disease frequency in a population as an early step attempted to planing, preventing, caring, and healing the disease. Objective: to determine the incidence rate of angular cheilitis at Dental Hospital of Jember University on October-December 2015, and the distribution based on age, sex, nutritional status, and residece. Method: This observasional descriptive study used cross sectional survey design. The study was conducted by identifying sample with angular cheilitis patient were found on October-December 2015 at Dental Hospital of Jember University. Result and conclusions: The incidence rate is 6,7%. The distribution based on age, sex, nutritional status and residence are most common in children 5-11 (89,2%), male (62,5%), malnutrition status (52%) and rural (59%), so that the rate is estimate the risk factor of angular cheilitis increase in children, male, malnutrition and villagers. Keywords: Angular Cheilitis, Distribution, Incidence